Dynamics of Customary Law in the Context of a Unitary State: A Case Study of Customary Areas in Konawe Regency - Hasjad Hasjad (Jurnal Restorasi : Hukum dan Politik, 2025)
This study aims to examine how customary law operates within the Unitary State of the Republic of Indonesia (NKRI), particularly in the customary areas of Konawe Regency, Southeast Sulawesi. Customary law is a legal system that thrives and continues to evolve within indigenous communities, often intertwined with state law. This study uses a juridical-sociological approach to examine how customary law is applied in community life, as well as how the state recognizes and incorporates customary law into the official legal system. The results show that although customary law still plays a role in resolving disputes and regulating social relations, the presence of state law, changes in societal structure, and government policies often diminish its influence. Furthermore, the lack of official recognition of customary territories has also impacted public trust in customary law. Therefore, efforts are needed to strengthen the role of customary law through appropriate policies and clear legal recognition, so that customary law can coexist alongside national law within the framework of the NKRI.